On Nonlinear Relationship between Inflation and Economic Growth: A Study of ASEAN-5 Countries Period 2000–2016 - Ambar Galih; Sugiharso Safuan (Economics and Finance in Indonesia, 2017)
Money (inflation) has played a vital role in economic growth. However, the nexus between them has always drawn mesmerizing debates. From the thoughts of Classical and Keynes which argued the existence of money neutrality, to the level of empirical studies which find either positive or negative correlation between inflation and economic growth. Recent studies concerning the debatable relationship have evolved it into a hypothesis whether the relation is nonlinear with a threshold or a point where the link switches. This study aims to re-examine the causality between inflation and economic growth in ASEAN-5 countries period 2000Q1–2016Q4. The results based on Threshold Vector Autoregression model indicate the presence of a nonlinear relationship between the two variables.